OPTIMALISASI KEBIJAKAN SISTEM PERADILAN PIDANA SECARA ELEKTRONIK DI MASA PANDEMI COVID-19 - Dewi Safitri (Universitas Muhammadiyah Tapanuli Selatan - Fakultas Hukum, 2021)
The world is currently experiencing very serious problems due to the emergence of the Covid-19 pandemic. Effects of Covid-19 has shifted conventional courts practice to online trial (e-litigation). This study aims to see growth on regulations and optimization of Electronic Criminal Justice Enforcement in this time. We use the normative juridical research with a constitutional and comparative approach. The Supreme Court Regulation Number 4 of 2020 concerning the Administration and Trial of Criminal Cases in Electronic Courts is a breakthrough as well as a commitment by law enforcers in realizing reforms in the Indonesian judiciary that synergize the role of information technology with procedural law in the current pandemic, in order to optimize the criminal justice system policy electronically it is necessary to carry out legal reforms through the revision of the criminal procedural law (KUHAP) into a new norm. which can be developed not only as a solution to current conditions, but it is also hoped that the policy can be permanent for the judiciary in realizing a supreme and modern technology based.